Knowledge assessment about risk prevention of rabies amongst doctors in AIIMS, Jodhpur - Kumar, Dewesh; Raghav, Pankaja Ravi; Singh, Mahendra; Bhardwaj, Pankaj (International Journal of Research in Medical Sciences, 2017)
Background:Rabies still continues to be a public health problem in India and to protect our citizens from this menace; medical professionals have to be well equipped to tackle it more efficiently. The paper aims to assess the knowledge of residents and faculty in newly established AIIMS regarding risk prevention of rabies. Methods:A cross sectional study using a structured questionnaire on rabies was done at AIIMS Jodhpur amongst the doctors and the data was compiled in Microsoft excel 2010 were further analysed using SPSS version 21. Results:Out of the total sixty respondents, faculty constituted 38.3%, and junior residents and senior residents 28.3% and 33.3% respectively. Nearly 72% responded correctly regarding post exposure prophylaxis (PEP) i.e. 5 dose regimen of intramuscular administration of Anti Rabies Vaccine (ARV) and 56.7% doctors were unaware about the current recommendation of intradermal (ID) route. Rabies immunoglobulin (RIG) or Anti-Rabies Serum (ARS) against Rabies infection used in Class III bites was known to only 45% of the total doctors. Conclusion:The study reveals that there is a scope of improvement in important areas related to the knowledge of doctors in AIIMS regarding animal bites which needs to be upgraded time to time through continuing medical education in order to follow the standard protocol and guidelines at the apex institute.